The effect of vehicle fuel economy standards on technology adoption - Thomas Klier; Joshua Linn (Federal Reserve Bank of Chicago, 2014)
Many countries are tightening passenger vehicle fuel economy standards. The literature on passenger vehicle standards has used structural models to estimate their welfare effects. This paper provides the first empirical evidence on the effects of recently tightened fuel economy standards on technology adoption. Specifically, it investigates changes in the rate and direction of technology adoption, that is, the extent to which technology is used to increase fuel economy at the expense of other vehicle attributes. We find that recent U.S. and European standards have both increased the rate of technology adoption and affected the direction of technology adoption. Producers reduced horsepower and torque compared to a counterfactual in which fuel economy standards remained unchanged. We estimate opportunity costs from reduced horsepower and torque to be of similar magnitude as the gains from fuel savings.
Keywords: L62; Q4; Q5; 330; passenger vehicles; U.S. greenhouse gas emissions rate standards; European carbon dioxide emissions rate standards; technology adoption